Effectiveness of Covid-19 Information through Social Media based on Public Intention - Dwi Yuniarto; Hasna Nazzala Khozinaturrohmah; Aedah Binti Abd. Rahman (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2021)
Corona Virus Disease-19 pandemic has changed people's habits today. Likewise, with the use of social media in terms of conveying information to the public. The government has now formed task forces in each region to prevent the spread of the virus. Among its duties is to convey information related to the prevention and spread of Corona Virus Disease-19. Considering that information delivery is deemed ineffective, some people do not fully know information about the Corona Virus Disease-19. The purpose of this study is to determine the effectiveness of information on Corona Virus Disease-19. To understand the relationship between the public's intention to end the Covid-19 pandemic and the effectiveness of Covid-19 information through social media the statistical analysis used is Cramer's V Non-Parametric Statistics, meanwhile, to find out whether the public's intention to end the Covid-19 pandemic affects the effectiveness of Covid-19 information through social media it is done through the partial least square approach. Questionnaire distribution via WhatsApp and made in google form to facilitate the distribution and filling. The number of responses was 401 respondents. The results obtained, the relationship between the latest education and attitudes when receiving hoax information and work relations with the frontline to end Corona Virus Disease-19 is that the community is declared insignificant, while the intention variable does not have a significant effect on the effectiveness factor. Different objects and respondents will be more interesting for further research as material for other researchers. Research results can be used as material for related parties, in this case the government to determine the media used to convey information about Covid-19.